Feasibility and Acceptability of a Chronic Disease Patient-Caregiver Network of Follow-Up Model for Local Caregivers, Phipun, Nakhon Si Thammarat Province:A Qualitative Study: Aranya Rakhab - Pongtriang, Praditporn; Rakhab, Aranya; Soontorn, Thassanee; Makyod, Wilawan (Princess of Naradhiwas University Journal, 2024)
The objective of this qualitative study was to evaluate the feasibility and acceptability of a Chronic Disease Patient-Caregiver Network (CDP-CN) of follow-up model in community. This innovative approach involved establishing a community - centered network of caregivers, focusing on identifying and managing patients with chronic diseases. The methodology encompassed the use of observation forms and semi - structured interviews with seven diabetes and hypertension patients and 15 caregivers, aiming to identify challenges, devise solutions, and evaluate the CDP - CN of follow -up model’s efficacy. Content analysis techniques were applied for data analysis. The findings of this study are significant, indicating that the CDP-CN of follow - up model is a viable and effective method for managing chronic diseases in communities. The model was adapted to fit the specific needs, flexibility and scalability. Particularly, training for caregivers and the establishment of a network system. It facilitated enhanced patient care in chronic disease management and led to notable improvements in healthcare access and management. A critical advantage of this model was its support for home-based health monitoring, which proved to be both time-efficient and cost-effective for patients and caregivers. Also, the model’s acceptability among all divers’ teams involved, including patients, caregivers, and healthcare providers due to enhance patient autonomy and empowerment. Additionally, the importance of a thorough follow-up visit system model was highlighted, emphasizing the need for continuous care. This comprehensive approach is crucial for delivering personalized, patient-focused care, especially for those with chronic conditions in community environments. The CDP - CN of follow-up model’s success illustrates its potential as a template for community healthcare initiatives, especially in managing chronic diseases in less urbanized areas. It emphasizes the importance of community-based care, local involvement, and multidisciplinary collaboration, offering an effective solution for improving chronic disease management and healthcare delivery.